Operation and characteristics of the Academic League of Pediatric Surgery in quaternary Center - Vaisberg, Victor Van; Cotrim, Fernanda Pereira; Ghaffar, Sumaya Abdul; Hara, Lucas Arjona de Andrade; Figueiredo, Roberta Monteiro; Tannuri, Uenis; Tannuri, Ana Cristina Aoun (Revista de Medicina, 2017)
Academic Leagues are student interest groups for the development and in-depth learning of a certain field of study, being the one most popular extracurricular in some Medical Schools. We present the Pediatric Surgery Academic League in a quaternary center in São Paulo, Brazil, where 23 students ranging from 2nd to 5th Medical School year are regular members, having regular activities such as visits to the operation room, outpatient clinic rotation, inpatient rounds and seminars. To be part of the Academic League, students have to pass a multiple question test based on an introductory course. In 2015, 65.00% of candidates were 1st year students, and the average grade obtained was 74.50%. Overall, we believe being a member of the Academic League promotes first exposure to a surgical specialty, greater workload in Pediatric Surgery, learning Semiology and development of teaching skills.